2005
DOI: 10.1097/00002030-200501280-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea exerts a cytostatic but not immunosuppressive effect on T lymphocytes

Abstract: Hyper-proliferation of T-lymphocytes is a major factor contributing to HIV pathogenesis. HU exerts a cytostatic effect on T lymphocytes, without altering their activation and apparently without having an immunosuppressive effect. The increase in cytokine production at the single cell level might compensate for the decrease in the percentage of activated CD4 T lymphocytes, without overall impairment of HIV-specific immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…S2e and f). HU has been reported to exert a cytostatic but not an immunosuppressive effect on T lymphocytes by not decreasing the production of T helper (h)1 or Th2 cytokines [42]. In our experience 4 did not affect TNF-α and IFN-γ (both Th1 cytokines) production.…”
Section: Figsupporting
confidence: 39%
“…S2e and f). HU has been reported to exert a cytostatic but not an immunosuppressive effect on T lymphocytes by not decreasing the production of T helper (h)1 or Th2 cytokines [42]. In our experience 4 did not affect TNF-α and IFN-γ (both Th1 cytokines) production.…”
Section: Figsupporting
confidence: 39%
“…Instead, hydroxyurea should not be used with stavudine, because of the demonstrated toxicity of this combination [35], nor with tenofovir, as data from our group show that in an animal model didanosine, tenofovir and hydroxyurea combination is fairly toxic (unpublished). enhanced by hydroxyurea after both Th-1 and Th-2 stimulation [57].…”
Section: Dose Finding Studies Of Hydroxyurea-didanosine Combinationmentioning
confidence: 90%
“…In fact one of the main concerns regarding the use of this combination in the clinical setting is that in patients treated with didanosine plus hydroxyurea the CD4 cell count increase was blunted compared to its antiviral effects. However, data from different groups have conclusively demonstrated that hydroxyurea blocks cellular proliferation but does not impede cellular activation nor diminish recall responses [57][58][59]. In a recent in vitro study [57] hydroxyurea reduced cell proliferation of both CD4 + and CD8 + T lymphocytes in a linear dose dependent manner.…”
Section: Hydroxyurea-didanosine Combination Is Not Immune Suppressivementioning
confidence: 99%
See 1 more Smart Citation
“…This combination has immune modulating activity and reduces viral targets (such as CD4 + T lymphocytes), possibly with limited immunosuppressive effects. Regarding the concerns of immunosuppressive effects of HU, several studies have demonstrated that HU blocks cellular proliferation but does not impede cellular activation nor diminish recall response [140,141]. In addition, suppression of immune activation by cytostatic drugs, such as HU, could complement cART.…”
Section: Immune-modulating Drugsmentioning
confidence: 99%